N-Bromo-succinimide promoted synthesis of β-carbolines and 3, 4-dihydro-β-carbolines from tetrahydro-β-carbolines. Issue 9 (2nd March 2016) - Hati, Santanu; Sen, Subhabrata
Graphical abstract: Abstract: Herein, we report a facile synthesis of 3, 4-dihydro-β-carbolines and aromatic β-carbolines from tetrahydro-β-carbolines, mediated by N -bromosuccinimide in toluene at 0 °C to room temperature (rt), in good to moderate yields.